2018
DOI: 10.1128/jvi.01621-17
|View full text |Cite
|
Sign up to set email alerts
|

A Y161F Hemagglutinin Substitution Increases Thermostability and Improves Yields of 2009 H1N1 Influenza A Virus in Cells

Abstract: Vaccination is the primary strategy for influenza prevention and control. However, egg-based vaccines, the predominant production platform, have several disadvantages, including the emergence of viral antigenic variants that can be induced during egg passage. These limitations have prompted the development of cell-based vaccines, which themselves are not without issue. Most importantly, vaccine seed viruses often do not grow efficiently in mammalian cell lines. Here we aimed to identify novel high-yield signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…2F ). In the 150-loop, a highly conserved tyrosine is present at position 161 in all HA subtypes except H7, H10, H12, H15, H17, and H18 ( 25 , 30 , 31 ). Previously, it was demonstrated that a Y161A mutation changed the binding properties of an H5 HA from NeuAc to NeuGc ( 17 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…2F ). In the 150-loop, a highly conserved tyrosine is present at position 161 in all HA subtypes except H7, H10, H12, H15, H17, and H18 ( 25 , 30 , 31 ). Previously, it was demonstrated that a Y161A mutation changed the binding properties of an H5 HA from NeuAc to NeuGc ( 17 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…N-glycan isoform microarray. The 83 N-glycans (41) were printed on N-hydroxysuccinimide (NHS)derivatized slides as described previously (42). All glycans were printed in replicates of six in a subarray, and eight subarrays were printed on each slide.…”
Section: Methodsmentioning
confidence: 99%
“…Two biotinlyated glycan analogs, 3ʹSLN and 6ʹSLN, were purchased from GlycoTech (Gaithersburg, MD, USA). Binding of viruses (at 5 nM/virus) to the biotinylated glycan analogs was performed as previously described [64] in an Octet RED96 biolayer interferometer equipped with streptavidin biosensor tips (PALL FortéBIO, Menlo Park, CA, USA). The glycan concentrations ranged from 0.007 μg/mL to 1.5 μg/mL.…”
Section: Methodsmentioning
confidence: 99%